Conservação de mandioca (Manihot esculenta Crantz) minimamente processada sob diferentes atmosferas modi-ficadas. - Silva, Josilene Amaro da (2009)
This study aimed to evaluate the use of modified atmosphere (MA) in the conservation of sweet cassava variety 'Pernambuana' minimally processed in plastic containers. In the first stage determined the chemical composition (macro and micronutrients), heavy metals, the cooking time (DTC), quality of cooking and cyanogenic compounds. Minimal processing was the subdivision into two areas, dirty areas: reception of raw materials, selection, classification and pre-wash. In the second step, the clean area: processing (peeling and cutting), rinse, sanitizing, spinning, packing, storage. We analyzed the gas concentration (O2 and CO2) inside the package by 70 pm. The experiment was conducted at temperature 10 °C and stored in polystyrene containers terephthalate (PET) without PVC (CONT), PET with PVC (AMCF), sealed polyethylene bags without vacuum (AMSV) and vacuum (AMCV) at 5 ± 0.2 º C, RH 43% for 20 days. Were performed physical and chemical analysis. The increase in browning (IE), staining of cuttings (L *, C *, H *). and enzyme activity were performed every four days until the 16th day. The microbiological analysis of fecal and total coliforms were performed on the day of processing, with eight and sixteen days. The variety 'Pernambucana‟ has got cooking time of 20 minutes, quality mass formed after cooking and low levels of cyanogenic compounds. It was observed that the pH, ascorbic acid, varied significantly during storage. There were statistical differences (P ≤ 0.05) for the values of reducing sugars, total soluble sugars during periods of storage. Packaging (AMSV and AMCV) had the highest values of L *, the lowest increment of darkening, a smaller reduction of ascorbic acid, however, had the highest pH values. The enzymes showed no statistical differences (P ≤ 0.05) for the activity of peroxidase and polyphenol in storage periods and between treatments. Considering the physico-chemical and microbial life of cassava was 12 days for treatments AMSVand AMCV and eight days for the treatment AMCF. According to the microbiological analysis of cassava breeding minimally processed showed an absence of coliform bacteria at 45 °C, however, treatment with AMCF, and AMSV AMCV showed total coliform counts considered high.